The Importance of the Expendable: Toxin–Antitoxin Genes in Plasmids and Chromosomes - Díaz-Orejas, Ramón; Espinosa, Manuel; Yeo, Chew Chieng (Frontiers in Microbiology, 2017)
Toxin-antitoxin (TA) genes were first reported in plasmids and were considered expendable genetic cassettes involved in the stable maintenance of the plasmid replicon by interfering with growth and/or viability of bacteria in which the plasmid was lost. TAs were later found in bacterial chromosomes and also in integrated mobile genetic elements; they were proposed to be involved in the bacterial response to stressful situations. At present, hundreds of TAs have been identified and classified in up to six families (I to VI), with those belonging to the type II (constituted by two protein components) being the most studied. Based on well-characterized examples of several type II TAs, we discuss in this review that irrespective of their locations in plasmids or chromosomes, TAs functionally overlap as indicated by: i) in both locations they can mediate the maintenance of genetic elements to which they are physical linked, and ii) they can induce persistence or virulence in response to stress situations. Examples of functional confluences in homologous TA systems with different locations are also given. We also consider whether the physiological role of TAs is due to their genetic organization as operons or to their inherent properties, like the short lifespan of the antitoxin component.